IκBα deficiency in brain leads to elevated basal neuroinflammation and attenuated response following traumatic brain injury: implications for functional recovery - Lian, Hong; Shim, David J; Gaddam, Samson SK; Rodriguez-Rivera, Jennifer; Bitner, Brittany R; Pautler, Robia G; Robertson, Claudia S; Zheng, Hui (Molecular neurodegeneration, 2012)
The transcription factor NFκB is an important mediator of cell survival and inflammation in the immune system. In the central nervous system (CNS), NFκB signaling has been implicated in regulating neuronal survival following acute pathologic damage such as traumatic brain injury (TBI) and stroke. NFκB is normally bound by the principal inhibitory protein, IκBα, and sequestered in the cytoplasm. Activation of NFκB requires the degradation of IκBα, thereby freeing NFκB to translocate to the nucleus and activate the target genes. Mice deficient in IκBα display deregulated and sustained NFκB activation and early postnatal lethality, highlighting a critical role of IκBα in NFκB regulation. We investigated the role of IκBα in regulating NFκB activity in the brain and the effects of the NFκB/IκBα pathway in mediating neuroinflammation under both physiological and brain injury conditions. We report that astrocytes, but not neurons, exhibit prominent NFκB activity, and that basal NFκB activity in astrocytes is elevated in the absence of IκBα. By generating mice with brain-specific deletion of IκBα, we show that IκBα deficiency does not compromise normal brain development. However, basal neuroinflammation detected by GFAP and Iba1 immunoreactivity is elevated. This leads to impaired inflammatory responses following TBI and worsened brain damage including higher blood brain barrier permeability, increased injury volumes and enlarged ventricle volumes. We conclude that, in the CNS, astrocyte is the primary cell type subject to NFκB regulation. We further demonstrate that IκBα plays an important role in regulating NFκB activity in the brain and a robust NFκB/IκBα-mediated neuroinflammatory response immediately following TBI is beneficial.